La prueba en los delitos de odio por motivos raciales - Janina Inés, Santacruz Morocho (2021)
Criminal law has among its functions, typify infractions and in turn establish a sanction for an action that violates any legal good protected by the State; Therefore, when a person commits a crime, he is criminally prosecuted, and after the trial, if both his responsibility and guilt are proven he is found guilty and a sentence is imposed, for this the judge must be convinced that the person charged is the author of the fact and reaches that conviction through the evidence practiced at the trial. Therefore, the importance of the evidence in the criminal process is vital, since through them the guilt or innocence of the prosecuted person will be demonstrated; The present project focuses on analyzing the evidence in hate crimes motivated by racial hatred, since it is a somewhat complex criminal type to prove and prove, since although the text of art. 177 of the Organic Integral Criminal Code, refers that the person who commits acts of physical or psychological violence of hate, is very subjective and difficult to verify that this action was committed for reasons of hate and hence the problem with this criminal type arises, the which in many occasions can remain in impunity for lack of evidence or in turn confuse the legal figure with other crimes such as injuries, psychological violence or discrimination.